Disability and sexuality in Makhanda, in the Eastern Cape: a comparative exploration of how black queer physically disabled individuals vs heterosexual physically disabled individuals negotiate their sexualities - Mzondo, Sinokuhle (Rhodes University, Faculty of Humanities, Department of Sociology)
The study aimed to comparatively explore the sexualities of queer disabled people and heterosexual disabled people. The objectives of the study were to comparatively explore their negotiation of romantic and sexual lives, comparatively explore the construction of sexual identities that intersect with disability, and offer an understanding of how both groups experience other people's perceptions of their identities. The social model of disability and queer theory were used to guide the study. The study was qualitative in nature. In-depth, semi-structured interviews were used to collect data. Three queer disabled and five heterosexual disabled individuals were interviewed. Thematic analysis methods were used to analyse the data. The findings of the study revealed how disability affected the romantic and sexual lives of the participants "“ both queer and heterosexual; their experience of others' perceptions of their identities, how they grew up with disabilities, how they adapted to their acquired disabilities, and the construction of their sexual identities.
Keywords: Sexual minorities -- South Africa -- Makhanda; College students with disabilities Sexual behavior; People with disabilities; Race discrimination; College students with disabilities Social conditions; Discrimination against people with disabilities